Heat Transfer Analysis of Passive Residual Heat Removal Heat Exchanger under Tube outside Boiling Condition - Yanbin Liu; Xuesheng Wang; Qiming Men; Xiangyu Meng; Qing Zhang (Science and Technology of Nuclear Installations)
The Passive Residual Heat Removal Heat Exchanger (PRHR HX) is an important part of the Passive Residual Heat Removal System (PRHRS). The C-shaped bundle is being used in the PRHR HX. A test facility of C-shaped tube immerged in a water tank was built to research the heat transfer of the PRHR HX. Through the experiments, three regions were found within a particular period of time during the heating process in the tank: natural convection region, transition region, and saturation boiling region. For the tube outside saturation boiling, comparisons of three different correlations in literatures with the experimental data were carried out. Results show that the Rohsenow correlation provides a best-estimate fit with the experimental results. For the tube outside transition region, a formulation is put forward to reduce error based on the Rohsenow subcooled boiling correlation.